3D anatomical modeling of the in vitro fertilization procedure and embryogenesis for medical education - Nyein, Chan Lwin (2013)
Understanding human embryo and fetus development is improved by the visualization of developing structures and spatial correlations of one stage to another over time. But most of the information available for the study is constrained to two- dimensions (2D), such as cross-sectional images, artistic drawings or tissue sections. Three-dimensions (3D) structure reconstruction approaches have attempted to resolve the problem of understanding this complex 3D process using 2D data. This project aims to investigate the potential benefits of using the latest 3D interactive & digital media technology for the modeling of anatomical structure and function to apply in medical education. The in vitro fertilization procedure, human embryo and fetus models were constructed from the photos and pictures. The softwares used in the project are (1) 3D Studio MAX for modeling, animation and rendering, movie effects and movie pre-visualization. There is also widespread usage of this software in biological and medical animation for teaching, simulating and demonstrating in various circumstances; (2) Windows Live Movie Maker, a software to make movies from photos and videos and adding special effects, transitions, sound, and captions to help create the story. This project will be an aid in medical education as the animation movie combined with labels and captions clearly explain the IVF procedure and development process of human embryo and fetus to aid students for better understanding.